Multivariate Statistical Analyses of the Temporal Variation in the Chemical Composition of the Essential Oil of Eucalyptus torquata in Cyprus - Mustapha Bulama Modu; Duygu Yiğit Hanoğlu; Azmi Hanoğlu; Fehmi Burak Alkaş; K. Hüsnü Can Başer; Dudu Özkum Yavuz (Molecules)
The genus Eucalyptus L’Hér., is native to Australia with 61 introduced taxa in Cyprus, including E. torquata Luehm., which has a wide distribution on the island. The aim of this study was to investigate the possible seasonal variations in the chemical composition of the essential oils of juvenile and mature leaves collected from Nicosia, Cyprus, by using multivariate statistical analysis. The leaves of 12 monthly collections were separately hydrodistilled, and GC-FID and GC/MS analyses were conducted. In general, the results revealed 1,8-cineole (mature: 3.6–27.8%; juvenile: 12.7–21.5%) and torquatone (mature: 27.6–48.8%; juvenile: 28.8–41.5%) as major compounds as well as an inverse relation between 1,8-cineole and torquatone content. Other important compounds found were α-pinene, β-eudesmol and α-eudesmol for all samples. The data support the existence of three major clusters, distinguished by the concentration of torquatone and miniatone. Minor compounds were also temporally relevant. The present study is among the first of its kind, analyzing the essential oils for a one-year period in Cyprus as well as conducting statistical analysis on E. torquata to reveal possible temporal variations between heterophyllous leaves, and also performing Hierarchical Cluster Analysis, determining the primary components of variability.